The wellness habits of men and women in the Northern Great Plain Region - Péter HIDVÉGI; Andrea Puskás LENTÉNÉ; József Márton PUCSOK; Melinda BÍRÓ; Kinga BÁRDOS (Editura Universităţii din Oradea, 2020)
In the past decades, the harmony of body and soul was getting more and more important, the balance, the self-confidence, and the positive-being, which is supported mostly by health tourism, so this section is improving with huge steps to serve the increasing needs fluently. For the effect of the consecutive social changes, the rules of genders have also changed. At the same time changes could be realized in the consumption habits of different genders. The resource took place from September to December 2018. It happened with a questionnaire survey; we asked the customers of hotels in the Northern Great Plain Region, and the answering was optional - they do it on their own choice. We investigated the participants' data through different dimensions and look for the answer to the question along these dimensions that which specifies had the service customers.